Anyone Muslim but everywhere Hallyu: Does religious commitment still matter in exerting consumer behaviors? - Alfian Budi Primanto; N. Rachma (Jurnal Manajemen dan Pemasaran Jasa, 2023)
The study explores the interaction between religiosity and global cultural adoption, particularly in the context of the Korean Wave, or Hallyu, which has seen a rapid surge in global popularity. Despite its widespread influence, there has been a lack of research on how religiosity intertwines with the acceptance of global culture in consumer behavior. This study aims to fill this gap by investigating the role of religious commitment in moderating the relationship between the credibility of Korean celebrities and consumer attitudes toward brands and advertising, as well as purchase intentions. Data was collected from 222 Muslim respondents across Islamic campuses in Indonesia, all familiar with popular K-pop groups such as Blackpink and BTS. Using the Preacher & Hayes method for analysis, the study revealed that celebrity credibility positively affects brand and advertising attitudes, as well as purchase intentions. However, the impact of brand and advertising attitudes was minimal, due to the repetitive of advertisements heavily focused on Korean celebrities without adequately emphasizing the value. Another crucial finding of the study was the non-significant influence of religious commitment in shaping consumer behavior. Although most respondents professed a commitment to the Islamic faith, many acknowledged inconsistencies in their religious practices and interactions with religious texts. This finding segues into a fascinating aspect of how respondents perceive the Korean Wave. Rather than viewing it through a religious lens, they see it as a cultural phenomenon. This delineation explains why religious commitment does not significantly influence their attitudes toward brands, advertisements, or purchase intentions.